Economic and biological characteristics of the spring bread wheat varieties developed in the Voronezh FASC named after V. V. Dokuchaev - E. I. Malokostova (Зерновое хозяйство России, 2021)
The current paper has discussed information on the characteristics and properties of the zoned spring bread wheat varieties developed in the Federal Agricultural Scientific Centre named after V.V. Dokuchaev. The purpose of the study was to develop new spring bread wheat varieties with high productivity and grain quality, resistant to unfavorable biotic and abiotic environmental factors and adapted to the conditions of the Central Blackearth Region. In the FASC named after V.V. Dokuchaev there were developed such highly productive spring bread wheat varieties as ‘Krestyanka’, ‘Kurskaya 2038’, ‘Voronezhskaya 12’, ‘Chernozemnouralskaya 2’ and ‘Voronezhskaya 18’, which are currently approved for use in production. There were analyzed the study results of productivity, grain quality and resistance to unfavorable environmental factors in different growing periods of the varieties. There was found an unambiguous productivity excess of the developed varieties over the standard ones. The endurance of the presented varieties in unfavorable conditions indicates an increase in the stability of the main traits that characterize productivity, resistance to drought, diseases, and lodging. There has been established, that in terms of grain quality the varieties ‘Krestyanka’ and ‘Chernozemnouralskaya 2’ belong to strong wheat with potential productivity of 7.20 and 6.65 t/ha, respectively. The varieties ‘Kurskaya 2038’, ‘Voronezhskaya 12’ and ‘Voronezhskaya 18’ are valuable wheat varieties with realized productivity potential of 5.31, 5.70 and 6.96 t/ha, respectively. There has been identified that the varieties ‘Chernozemnouralskaya 2’ and ‘Voronezhskaya 18’ are recommended to sow with a seeding rate of 6.0 million germinating grains per hectare for the rapid seed reproduction and obtaining high gross grain yield, since productivity, yield of conditioned seeds, germination and 1000-grain weight at this rate was the best. The sowing dates of these varieties were early.